Optimised Design of Network Intrusion Detection System (NIDS) using HDL - Singh, Sachin; Sharma, ND (International Journal of Computer Sciences and Engineering, 2025)
This paper covers the implementation of the implementation of Network Intrusion Detection System (NIDS) using International Data Encryption Algorithm (IDEA). The current era has seen an explosive growth in communications. Applications like online banking, personal digital assistants, mobile communication, smartcards, etc. have emphasized the need for security in resource constrained environments. International Data Encryption Algorithm (IDEA) cryptography serves as a perfect network intrusion detection system (NIDS) tool because of its 128 bits key sizes and high security comparable to that of other algorithms. However, to match the ever increasing requirement for speed in today‟s applications, hardware acceleration of the cryptographic algorithms is a necessity.